High-resolution investigations of fault architecture in space and time - Leonardo Del Sole; Giulio Viola; Luca Aldega; Vincenzo Moretto; Manuel Curzi; Ruikai Xie; Luigi Cantelli; Gianluca Vignaroli (Scientific Reports)
Abstract Heterogeneous fault architecture affects crustal seismotectonics and fluid migration. When studying it, we commonly rely on static conceptual models that generally overlook the absolute time dimension of fault (re)activation. Heterogenous faults, however, represent the end-result of protracted, cumulative and intricate deformation histories. This may lead to inaccurate reconstructions of tectonic histories and flowed models of fault hydro-mechanical behavior. We adopt here a multitechnique approach building upon the examination of now juxtaposed but not coeval brittle structural facies (BSF), which offer multiscalar insights in the spatio-temporal-thermal fault evolution. Our approach is applied to the Carboneras Fault, unveiling a ~ 25 Myr-long polyphase structural and thermal evolution. This led to a complex fault architecture, where BSFs exhibit a stark heterogeneity in fault rock and permeability, ultimately generating very different space- and time-dependent fault hydro-mechanical behaviors. Therefore, fault architectures shall be seen as dynamic features from which to extrapolate time-integrated comprehensive fault models accounting for the entire deformed rock volume and fault life span. We demonstrate that high-resolution studies of fault architectures are required to elucidate modes of fault growth and evolution, decipher long-lived, polyphase tectonic and thermal histories, and understand the influence of heterogenous fault architecture on hydraulic compartmentalization and earthquake rupture dynamics.